Strategic Investment Decisions and Their Implications for Firm Value: A Mediated Model of Dividend Policy - Purbasari, Intan (Eastasouth Institute, 2025)
This empirical analysis explores the relationship between investment decisions, proxied by PER, and dividend policy, proxied by DPR, on firm value, as indicated by PBV, within manufacturing sector firms listed on the Indonesia Stock Exchange from 2015 to 2021. Firm value serves as the dependent variable, while investment decisions act as the independent variable, and dividend policy functions as a mediating variable. The research population comprises pharmaceutical companies listed on the IDX within the specified period, with samples selected through purposive sampling based on the criteria of consistently publishing audited financial and annual reports. The study employs descriptive statistical analysis and path analysis, an extension of multiple regression techniques. The empirical findings demonstrate that investment choices contribute meaningfully and positively to the firm's market performance. Nonetheless, investment decisions do not exhibit a statistically significant effect on dividend policy, nor does dividend policy have a notable influence on corporate value. In addition, mediation analysis indicates that dividend policy does not serve as an intervening variable in the linkage of investment decisions and corporate value.